Trifluoromethyl ketone P3HT-CNT composites for chemiresistive amine sensors with improved sensitivity - Kim, Yeong Gyu; Oh, Byeong M.; Kim, Haneul; Lee, Eun Hye; Lee, Dong Hyun; Kim, Jong H.; Koo, Byungjin (Sensors and Actuators B: Chemical, 2022)
Chemiresistive sensors, wherein conductivity is changed by exposure to analytes, are widely used in various disciplines and in our daily lives. Carbon nanotubes (CNTs) are excellent materials with exceptional conductivity, and polymer/CNT composites have been extensively deployed in chemiresistive sensors. To improve sensitivity, we herein report the covalent functionalization of poly(3-hexylthiophene)s (P3HTs) with highly electrophilic trifluoromethyl ketones, referred to as TFMK-P3HT, and its composite with CNT and amine sensing were investigated. The synthesis was begun with the bromination of commercial P3HT, followed by a lithium-halogen exchange reaction and subsequent quenching with trifluoroacetic anhydride, producing TFMK-P3HT. Homogeneous CNT networks with TFMK-P3HT were confirmed by atomic force microscopy (AFM). The sensing of three representative amines with TFMK-P3HT/CNT showed four times higher sensitivity than P3HT/CNT samples. The sensors were selective to amines and less responsive to competitive gas species such as alcohols and H2S. The sensitivity improvements of the TFMK-P3HT sensor were maintained in humid conditions. This work suggests a facile synthetic method to improve the sensitivity of CNT-based chemical sensors and provides an effective gas sensor platform for the selective detection of amine gas.
Keywords: Amine sensors; Analytes; Carbon nanotube sensor; Carbon nanotubes composites; Chemiresistive sensors; Daily lives; Nanotube sensors; P3HT; Polymer/carbon nanotube composites; Trifluoromethylketone; Amine sensor; Carbon nanotube; Chemical sensor; CNT sensor; Fluorination; P3HT